Atomic-level insight into process and mechanism of ion beam machining on aluminum optical surface - Du, Chunyang (2024)
Polycrystalline Al workpieces go through a complex surface atom sputtering and surface/subsurface atom diffusion throughout the ion beam machining process that plays a critical role in determining machining quality of optical mirror surfaces. Here, we leverage molecular dynamics method for the first time to reveal the machining mechanism and the polycrystalline effect of aluminum during ion beam sputtering, in term of cascade collision, atom trajectory, sputtering yield, and surface characteristic. Polycrystalline Al presents a significant low potential energy state, leading to milder cascade collision and weaker sputtering effects than monocrystalline Al during ion beam machining. The atom trajectory demonstrates irregular variation as the atom diffusion is blocked by grain boundary (GB) in polycrystalline Al, leading to the relief microstructure and poor surface quality. With incident ions increasing, the GBs are broken and atom diffusion enhancing, as well as lower subsurface defects and better finishing surface quality. The microscopic morphology evolves into gravel microstructure. Simulation results also reveal that atom diffusion will benefit from high ion concentration and low ion energy. Sputtering yield variation is more sensitive to ion energy. To acquiring better finishing surface quality of Al without influencing machining efficiency, ion concentration must be increased while the ion energy needs to be decreased appropriately but a large number of cascading collisions need to be ensured.